Tragsessel in europäischen Herrschaftszentren Vom Spätmittelalter bis Anfang des 18. Jahrhunderts - Álvarez, Alejandro López; Döberl, Mario (2020)
For the first time, this anthology is dedicated to the early days of baby armchairs in Europe. It contains seven articles by international researchers who deal with the history of the introduction and establishment of armchairs in various European centers of power. Carrying chairs are fascinating objects that elude conventional categorizations in many ways. On the one hand, they can be assigned to the furniture area - at least in their simplest design - but on the other hand they are also a means of transport. In a simple, robust design, armchairs were inexpensive everyday vehicles in city traffic that could be rented for short distances. In precious furnishings, on the other hand, they were courtly showpieces, which eminently symbolized social differences of the civil society: representatives of the upper class were transported in their palaces or on the streets of the city by servants dressed in precious liveries, rose above the unclean ground and symbolically caught up with the common people.